INOVASI METODOLOGI PEMBELAJARAN PAI DALAM MENINGKATKAN MUTU PENDIDIKAN - Haditsa Qur'ani Nurhakim (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Islamic Religious Education plays a strategic role in shaping students' character, morality, and spiritual competencies. However, the implementation of PAI learning still faces various challenges, including low student participation, the dominance of lecture-based teaching methods, and the limited utilization of technology and innovative learning approaches. This article aims to analyze the importance of innovation in PAI learning methodologies to improve educational quality and to identify various innovative approaches that can be implemented in the learning process. The study employs a library research method by reviewing relevant scientific literature, books, and previous research findings related to PAI learning and educational innovation. The results indicate that the application of innovative learning methods, such as Project-Based Learning, Problem-Based Learning, collaborative learning, and the integration of digital technology, can enhance students’ engagement, motivation, conceptual understanding, and critical thinking skills. Furthermore, innovation in PAI learning methodologies contributes to creating a more interactive, contextual, and student-centered learning process. Therefore, educators need to continuously develop their pedagogical competencies and utilize various innovative approaches to achieve the objectives of Islamic Religious Education effectively. This article provides a conceptual contribution to the development of PAI learning methodologies that are relevant to the demands of twenty-first-century education.